Three-Drug Combination Regimen in Pancreatic Cancer Treatment: Are We There Yet? - Kang, Soonmo Peter; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
No abstract available. Image: Herbert Irving Cancer Center. New York, NY, USA